Impact of chronic alcohol exposure on conventional and regulatory murine T cell subsets - Paterson, Cameron W.; Gutierrez, Melissa B.; Coopersmith, Craig M.; Ford, Mandy L. (Frontiers in Immunology, 2023)
Chronic alcohol use poses significant negative consequences to public health and, among its many biologic effects, is associated with significant T cell dysregulation within the adaptive immune system that has yet to be fully characterized. Novel, automated strategies for high dimensional flow cytometric analysis of the immune system are rapidly improving researchers’ ability to detect and characterize rare cell types. Using a murine model of chronic alcohol ingestion in conjunction with viSNE and CITRUS analysis tools, we performed a machine-driven, exploratory analysis comparing rare splenic subpopulations within the conventional CD4+, regulatory CD4+ and CD8+ T cell compartments between alcohol- and water-fed animals. While there were no differences in the absolute numbers of bulk CD3+ T cells, bulk CD4+ T cells, bulk CD8+ T cells, Foxp3- CD4+ conventional T cells (Tconv) or Foxp3+ CD4+ regulatory T cells (Treg), we identified populations of naïve Helios+ CD4+Tconv and naïve CD103+ CD8+ splenic T cells that were decreased in chronically alcohol exposed mice versus water-fed controls. In addition, we identified increased CD69+ and decreased CD103+ eTreg subsets in conjunction with increased frequency of a population that may represent a transitional phenotype between cTreg and eTreg. These data provide further resolution into the character of decreased naïve T cell populations known to be present in alcohol exposed mice, as well as describe alterations in effector regulatory T cell phenotypes associated with the pathogenesis of chronic alcohol-induced immune dysfunction.